Efficacy of combining intravitreal injections of ranibizumab with micropulse diode laser versus intravitreal injections of ranibizumab alone in diabetic macular edema - Khalil, Hisham Fawzy; Ali, Mahmoud Mohammed Ahmed; Rahman, Ahmed Fasial Abdel (International journal of health sciences, 2022)
Background: Diabetic retinopathy (DRP) and diabetic macular edema (DME) are diseases of the retina that are caused by complications of diabetes mellitus. Aim and objectives: the aim of the study was to evaluate the efficacy of combining intravitreal injections of ranibizumab with micropulse laser versus intravitreal injections of ranibizumab alone in diabetic macular edema. Subjects and methods: This prospective, randomized, comparative, interventional and hospital-based study was carried out in ophthalmology department of Al Azhar university hospitals and Kobry El Qobba Military specialized eye hospital, Cairo, Egypt. The study included 80 eyes of diabetic macular edema were divided into two groups, each of them included 40 eyes:Group 1: Patients with diabetic macular edema underwent three intravitreal injections of ranibizumab alone. Group 2: Patients with diabetic macular edema received one intravitreal injection of ranibizumab with two sessions of adjuvant micropulse diode laser.The duration of the study ranged from 6-12 months. Results: there is statistically significant increase in the best corrected visual acuity after treatment than before treatment. Further analysis demonstrated that visual acuity at 3 and 6 months of follow up were statistically significantly higher than visual acuity before treatment in diabetic patients with macular edema who received ranibizumab and laser therapy.